Fetal and Neonatal Outcomes of Maternal Rheumatic diseases in a tertiary care centre of Lahore, Pakistan - Saqib Aslam, Faiza Yasin, Saadat Ullah, Muhammad Haroon, Zahid Anwar, Rafia Gul (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregnancy may worsen underlying autoimmune rheumatologic illnesses. The trans-placental transmission of autoantibodies can harm the foetus or newborn. Aim: To determine the impact of maternal rheumatological disorders on fetal and newborn outcomes. Methods: A descriptive longitudinal study was conducted at Fatima Memorial Hospital enrolling 32 pregnant women with rheumatologic disorders by consecutive sampling. Data was collected regarding maternal demographics, diagnosis, serum markers, Fetal & neonatal outcome factors (IUGR, Fetal distress, Umbilical Doppler findings, Fetal Echo, Place of birth, Mode of delivery, discharge status, Term/pre-term birth, Gender, Low Birth Weight, Cardiac defect, NICU stay, the reason for NICU stay) Results: The diagnosis of 50% of the subjects was SLE. 25%subjects were suffering from RA. Regarding serum markers, 50% of the mothers were Anti ds DNA positive followed by ANA with 34.4% & Lupus anticoagulant with 21.9% positivity. IUGR was recorded in 9.4%, fetal distress in 28.1%, abnormal umbilical doppler in 9.4%, and 12.5% of a newborn could not survive. Pre-term delivery was recorded in 31.3% of cases, low birth weight in 34.4%, cardiac defects in 6.3%, thrombocytopenia in 6.3%, NICU stay was required in 31.3%, EOS was reason in 12.5% and RDS in 25%. Conclusion: Prevalence of IUGR, fetal distress, low birth weight, preterm delivery, cardiac defects and admission to NICU was high in autoimmune rheumatological pregnant females. Pre-term delivery, fetal distress and LBW were significantly associated with SLE. Keywords: Pregnancy outcome, rheumatic disease outcome, fetus, neonate, SLE